1994
DOI: 10.1007/bf02053601
|View full text |Cite
|
Sign up to set email alerts
|

Perianal actinomycosis—A complication of a fistula-in-ano

Abstract: Perianal actinomycosis is a rare complication of fistula-in-ano. We report a case of an 82-year-old male with an atypical fistula that had an internal opening at a posterior crypt and, over an extense perianal and gluteal area, induration with multiple suppurative draining sinus tracts. He underwent fistulotomy and an ample excision of the diseased areas. The pathology report was actinomycosis. Further treatment with antibiotics was continued until the patient was clinically cured. The diagnosis of perianal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
7

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 6 publications
0
17
0
7
Order By: Relevance
“…[23][24][25] Primary anorectal and perianal actinomycosis are very rare. [14][15][16][17][18][19][20][21][22][26][27][28][29] According to Cope, 26 infection with Actinomyces species occurs so seldom in the colon and the anorectum that no surgeon, even a proctologist, is likely to see more than a few cases in a lifetime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Primary anorectal and perianal actinomycosis are very rare. [14][15][16][17][18][19][20][21][22][26][27][28][29] According to Cope, 26 infection with Actinomyces species occurs so seldom in the colon and the anorectum that no surgeon, even a proctologist, is likely to see more than a few cases in a lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…23 The male predominance in perianal actinomycosis also is striking, an observation consistent with our findings. [14][15][16][17][18][19][20][21][22] The pathophysiology of actinomycosis remains partially unexplained. In humans, Actinomyces israelii colonizes the mouth, oropharynx, and vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Morson [11]first described this condition in 1961, and suggested that all rectal strictures should be biopsied for exclusion of this infection. Primary rectal actinomycosis in association with perirectal abscesses and perianal fistulae has been reported [12, 13]. Until 1986, two additional cases of pelvic actinomycosis presenting with rectal stricture were reported [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Hydronephrosis due to extrinsic compression of the actinomycotic granuloma has also been reported [6,7,11]. Anorectal and hepatobiliary primary actinomycosis have already been described in the literature (16)(17)(18). The involvement of multiple organs, such as in this patient, is rare but has been previously reported [6,7,19].…”
Section: Discussionmentioning
confidence: 67%